TOXICITY STUDIES OF PHOTO-FILM WASTES - Krishnamoorthi, K P; Deshpande, W M; Mohanrao, G J (Indian Journal of Fisheries, 2011)
The photo-film industry discharges three types of wastes, all of which are toxic to fish to some extent. The effluents in descending order of toxicity are the laboratory effluent, the emulsion wash water, and the white water, with their respective 48 hr TLm concentrations at 1, 5 and 10 per cent. A mixture of the wastes composited on the basis of their flows had a 48 hr TLm of 5 per cent. Toxicity of the emulsion wash water was primarily due to the undissociated ammonia. Laboratory effluent toxicity was primarily due to hydroquinone and metol which showed synergistic effects. Thiosulphate and carbonate and to a much smaller extent sulphate had antagonistic effects on the toxicity of hydroquinone and meto!. Coagulation with aluminium sulphate and settling reduced tlie toxicity of the wastes considerably.